Reactivity indexes for different geometries of palladium leads - Gómez Carrillo, Sandra Carolina (2009)
Electronic transport through metallic break junctions or molecules is clearly dependent not only on the electronic structure of the central nanodevice connecting the leads, but also the shape and crystalline orientation of the contacts which can define the possible conduction channels. In this work we examine different geometries of contacts of palladium characterizing them through global and local reactivity indexes as electrophilicity, chemical hardness and Fukui functions. In molecules, these indicators are essentially defined by the energies of the frontier molecular orbitals and in solids they are related with the local and partial density of states. We use for this purpose an ab-initio based code (FIREBALL), applied to plane contacts with (001) fcc faces and also pyramidal tips grown following a (001) and (111) packaging. The results allow us to have an insight about the chemical features of this type of nanojunctions.